A Predictive Score for Bullying-Related Burnout in Healthcare Professionals: Implications for Organizational Interventions in Indonesia - Amanda, Vita; Niama Nina Indolo; Andi Fatihah Syahrir; Tiffany Gabrielle (Scientia Psychiatrica, 2024)
Introduction: Workplace bullying is a pervasive issue with detrimental effects on the mental health and well-being of healthcare professionals. This study aimed to develop and validate a predictive score for bullying-related burnout among healthcare professionals in Indonesia and explore its implications for organizational interventions. Methods: A cross-sectional study was conducted involving 785 healthcare professionals from various hospitals in Indonesia. Data were collected using self-reported questionnaires, including the Indonesian versions of the Negative Acts Questionnaire-Revised (NAQ-R), the Copenhagen Burnout Inventory (CBI), and the Workplace Bullying Scale (WBS). Sociodemographic and work-related factors were also assessed. Multiple linear regression analysis was used to develop the predictive score, and its performance was evaluated using receiver operating characteristic (ROC) curve analysis. Results: The prevalence of workplace bullying was 32.1%, with verbal bullying being the most common type. Burnout was significantly associated with bullying experiences (p<0.001). The final predictive score included age, gender, profession, years of experience, work hours per week, perceived social support, and exposure to different types of bullying. The score demonstrated good predictive accuracy (AUC=0.88, 95% CI: 0.84-0.90) for identifying individuals at high risk of burnout. Conclusion: This study provides a validated predictive score for bullying-related burnout in Indonesian healthcare professionals. The score can be used to identify high-risk individuals and guide targeted organizational interventions to prevent and mitigate the negative consequences of workplace bullying.